(untitled) (Biological Sciences - PJSIR, 2007)
The fats prod uced as a resul t of hydrogenation of the oi ls of three varieties of mango kernel ( Mangi(era i11d ica), We re fou n d tO COn Si St Of / rans fatty acids, C , (0. 02-0.60 o/o) , CIM: I (2. 69-4.48 o/o) ,ClO : I (0.02-0. 04 o/o) , C , 16 1 (traces-0.05 %), C2 ,. 1 ( traces-0.02 %) i n add i ti on to cis fa t ty acid s.